Diskursus Hadis dalam Perspektif Kaum Tua dan Kaum Muda di Indonesia - Rozian Karnedi (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2022)
Abstract: The article sheds light the discourse of ḥadīth in the horizon of the mid-twentieth century reformist (kaum muda) and traditionalist (kaum tua) Muslim. It aims to analyze debates and different stances concerning with the use of the ḥadīth and the epistemic view behind their conception of ḥadīth. The study approaches with the basic theories of muṣṭalāḥ al-ḥadīth and the sociology of knowledge of Karl Mannheim. The research data were processed through descriptive-comparative and critical-analysis. It then argues that there are two different characteristics between the reformist and the traditionalist in the use of ḥadīth. First, the reformist used to have a systematic study based on the Qur’an and ḥadīth directly, while the traditionalist used to bring the idiomatic (‘ibārah) method. Second, in deducing law (istinbāṭ al-aḥkām), the reformist restrict only on the boundary of the authentic ḥadīth. Meanwhile, besides using authentic ḥadīth, the traditionalist also accept the unsound ḥadīth for the sake of the venture of goodness (faḍā’il al-a‘māl) with certain conditions. These differences are not only caused by methodological enterprise and scientific genealogy, but also sociological consideration which leads to the contestation (conflict of thought) between the two of them regarding the issue of taqlīd, ijtihād, ittibā‘, bid‘ah and religious traditions.   Abstrak: Artikel ini menyoroti wacana hadis dalam cakrawala Muslim reformis (kaum muda) dan tradisionalis (kaum tua) pada pertengahan abad ke-20. Tulisan ini bertujuan untuk menganalisis perdebatan dan perbedaan pendapat tentang penggunaan hadis dan landasan epistemik di balik konsepsi mereka tentang hadis. Kajian ini menggunakan pendekatan keilmuan hadis dan sosiologi ilmu pengetahuan Karl Mannheim. Data penelitian diolah dengan menggunakan metode deskriptif-komparatif dan analisis kritis. Artikel ini berargumen bahwa ada dua karakteristik yang berbeda antara kelompok kaum muda dan kaum tua dalam penggunaan hadis. Pertama, kaum muda umumnya memiliki kajian sistematis yang bersumber langsung dari al-Qur’an dan hadis, sedangkan kaum tua seringkali menggunakan pendekatan idiomatik (‘ibārah). Kedua, dalam menarik kesimpulan hukum (istinbāṭ al-aḥkām), kaum muda membatasi hanya pada hadis yang sahih. Sementara itu, kaum tua, selain menggunakan hadis sahih, juga menerima hadis-hadis ahad, atau bahkan daif, untuk kepentingan amal kebaikan (faḍā’il al-a‘māl), namun dengan syarat-syarat tertentu. Perbedaan tersebut tidak hanya disebabkan oleh kerangka metodologis dan latar genealogi keilmuan, namun juga pertimbangan sosiologis, yang berujung pada kontestasi (konflik pemikiran) terhadap persoalan-persoalan khilafiyah seperti taklid, ijtihad, ittibā‘, bidah dan tradisi keagamaan.